2002
DOI: 10.1111/j.1572-0241.2002.07100.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable Stiffness Colonoscopes Are Associated With Less Pain During Colonoscopy in Unsedated Patients

Abstract: Our results indicated that VSC allows favorable examination compared with CC regarding completeness, time to cecal intubation, and comfort of patients undergoing unsedated colonoscopy, irrespective of the examiner's experience. These features suggest VSC as the preferred colonoscope for patients undergoing unsedated colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In the sedated patients, the use of a variable-stiffness colonoscope significantly minimized procedure-related pain [14,15], reduced the dose of sedative medications during colonoscopy [15], and shortened cecal intubation time [14]. In the unsedated patients, the variable-stiffness colonoscope allowed favorable examination compared with conventional colonoscope regarding completeness, time to cecal intubation, and comfort of patients undergoing colonoscopy, irrespective of the examiner's experience [6]. The completion rate markedly improved after switching from an adult colonoscope to a small caliber variable-stiffness colonoscope in difficult or incomplete colonoscopies, although the small caliber variable-stiffness colonoscope did not appear to offer any advantage over the adult colonoscope for routine colonoscopies [16].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the sedated patients, the use of a variable-stiffness colonoscope significantly minimized procedure-related pain [14,15], reduced the dose of sedative medications during colonoscopy [15], and shortened cecal intubation time [14]. In the unsedated patients, the variable-stiffness colonoscope allowed favorable examination compared with conventional colonoscope regarding completeness, time to cecal intubation, and comfort of patients undergoing colonoscopy, irrespective of the examiner's experience [6]. The completion rate markedly improved after switching from an adult colonoscope to a small caliber variable-stiffness colonoscope in difficult or incomplete colonoscopies, although the small caliber variable-stiffness colonoscope did not appear to offer any advantage over the adult colonoscope for routine colonoscopies [16].…”
Section: Resultsmentioning
confidence: 97%
“…A recent review of unsedated endoscopy [1] by examining a selection of reports [2][3][4][5][6][7] concluded that the scant amount of literature on unsedated colonoscopy makes the assessment of its feasibility and acceptability difficult. That sedated colonoscopy is usual practice and unsedated colonoscopy has limited acceptance in the United States is confirmed by the result of a recent survey of 18% of the members of the American Society of Gastrointestinal Endoscopy [8].…”
Section: Introductionmentioning
confidence: 98%
“…There are several reports on the basis of patient tolerance during colonoscopy with regard to different types of colonoscopes [10,[16][17][18][19]. According to the previous reports, patient tolerance during colonoscopy with regard to different types of colonoscope is still a matter of debate.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, if the procedure is performed by an in-experienced endoscopist, the differences would be amplified [25,26].…”
Section: Discussionmentioning
confidence: 99%